The New Feminist Movement in the Nordic Countries in the 1970s - Sigríður Matthíasdóttir (Veftímaritið Stjórnmál og stjórnsýsla, 2012)
This article discusses some recent studies of the New Women’s Movement in Sweden, Norway and Denmark in the 1970s. The article is mainly based on studies by the Swedish historians Elisabeth Elgán and Emma Isaksson the Norwegian historians Trina Rogg Korsvik and Gro Hagemann and the Danish political scientist Drude Dahlerup, all of whom have been prominent in this field in recent years or written important articles on the subject. They have written, for example, about the movement’s "story of origins" in each country, the methods that were used in the struggle for equality, ideology and the movement’s connection with equal-rights campaigns in other countries, especially the USA. The "story of origins" is re-evaluated. It is interesting to see how descriptions of the various public "actions" reflected the women’s ideas on the question of equality. The aim of the struggle was to increase equality in society, and naturally this had significant political implications, which proved to be a cause of friction and dissension when socialist and radical feminist ideologies came into conflict. The purpose here is to discuss specific factors that shaped the struggle, look into the ideology that it was based on and examine some of the developments that took place in these three countries. Relevant examples are cited from the equal-rights campaign of the Icelandic "Red Stockings Movement" (Rauðsokkahreyfingin). Some questions are put forward at the end regarding the movement in Iceland and its similarities to the movements in other Nordic countries. Considerably more research in the field in Iceland will be needed before it is possible to answer these questions.